Comparison between Scalpel Incision and Diathermy Incision in Elective Midline Abdominal Surgery - Akram, Sarmad; Javed, Irfan; Hussain, Muhammad Irshad; Muhammad, Faizan; Yousaf, Noman; Batool, Shaista; Ilyas, Haseeb; Haider, Sarfaraz Hussain; Rehman, Abdul; Usman, Nida (Indus Journal of Bioscience Research, 2025)
Introduction: Midline abdominal surgeries also need an accurate approach toward appropriate incisions to ensure safer surgery and better results. The scalpel has been used in the past, but there is evidence showing that diathermy incisions have certain benefits, both in blood loss and incision time. This study compares the efficacy and safety of these two techniques. Objectives: The aim was to compare between scalpel and diathermy incisions in terms of incision time, intraoperative blood loss, postoperative pain, and wound healing in elective midline abdominal surgeries. Materials and Methods: This randomized controlled trial occurred in Recep Tayyip Erdogan Hospital, Muzaffargarh, from 15 September, 2024 to 14 March, 2025. A total of 102 patients were selected and randomized as the scalpel group and diathermy group. Incision time, blood loss, postoperative pain (Measuring by VAS), and wound healing were recorded in the SPSS v.25 software and analyzed. Results: Diathermy also had the added advantages of reducing the incision time and the amount of blood loss compared to the scalpel. The Diathermy treatment group recorded fewer pains than the control group on the days after the operation. There is no significant difference between wound healing and surgical site infections. Conclusion: Diathermy incisions make surgery more effective and less uncomfortable for the patient without adding to the risk factors which are always associated with scalpel incisions.